2018
DOI: 10.5430/jnep.v9n2p37
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ communication with dying children and their families in pediatric oncology: A literature review

Abstract: The last period of life for a child dying from cancer is of critical importance, not only for the child, but also for the child’s parents and other relatives. Health care professionals, especially nurses, face multiple challenges when caring for children dying from cancer. By better understanding the conversational topics that arise in the care of children dying from cancer and their families, nurses may best manage the communication challenges that arise during this difficult time of suffering. This literatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…However, contrary to these findings, other studies indicated that nurses around the globe are knowledgeable and play a vital and central role in the delivery of all cancer treatment modalities, principally surgical, radiation, and medical oncology. For patients undergoing surgical intervention, nurses teach patients what to expect before, during, and after procedures [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…However, contrary to these findings, other studies indicated that nurses around the globe are knowledgeable and play a vital and central role in the delivery of all cancer treatment modalities, principally surgical, radiation, and medical oncology. For patients undergoing surgical intervention, nurses teach patients what to expect before, during, and after procedures [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…However, contrary to these ndings, other studies indicated that nurses around the globe are knowledgeable and play a vital and central role in the delivery of all cancer treatment modalities, principally surgical, radiation, and medical oncology. For patients undergoing surgical intervention, nurses teach patients what to expect before, during, and after procedures (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…However, contrary to these ndings, other studies states that nurses around the globe are knowledgeable and play a vital and central role in the delivery of all cancer treatment modalities, principally surgical, radiation, and medical oncology. For patients undergoing surgical intervention, nurses teach patients what to expect before, during, and after procedures (33,34).…”
Section: Discussionmentioning
confidence: 99%